PEMANFAATAN OROK-OROK (Crotolaria Juncea) MENDUKUNG PERTANIAN BERKELANJUTAN - Tience E. Pakpahan (Universitas Pembangunan Panca Budi, 2018)
Sun hemp (Crotalaria juncea) is a cover crop that is shaped like a bush and is useful as a green manure. The advantages of sun hemp are serves as a source of organic material, the source of nitrogen through the association of N-fixation bacteria on the root nodule will increase the nutrients in the soil. This serves to provide N for the crops, although not entirely, to improve the nutrient cycling and soil conservation: deep-rooted green manure can help raise the nutrients that have been leached or washed from the soil surface. Sun hemp can also be useful in suppressing weed growth because it has allelopathic compounds that showed by its dominant population, and it is useful to reduce the endoparasitic population attached to the nematodes, which live somewhere and eat the roots throughout its life cycle. Utilization of the sun hemp as fertilizer can be sustainable, it needs to be done multiplication. Planting of sun hemp besides taken forage for fertilizer, also taken the seeds for the next planting material. The seeds should be harvested from old seeds. Seeds are dried, separated from dirt, and put into plastic bags. By default, 1000 seed grains are 41,731, so 1 kg can fill 24 thousand sun hemp seeds plants. The greatest nitrogen content at the beginning of flowering, the initiation of flowers until mid-bloom, and decreases because N reserves are allocated for seed formation. A sustained increase of agricultural production becomes a great possibility for all. In this process a green manure crops application for using usun hemp get a new chance for improvement process on sustainable agriculture.